Solid electrolyte coating diaphragm, preparation method thereof and lithium ion battery
By using solid electrolyte coating technology of LLZTO and Si3N4 in lithium-ion battery separators, the existing separators have insufficient heat resistance and low peel strength in the high temperature range, and the battery has high heat resistance, low internal resistance and long cycle life.
Patent Information
- Application Number
- CN202411872386.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
The existing ceramic/organic coated separators have poor heat resistance in the high temperature range (T>150°C), which leads to a decrease in the lithium ion passing rate of the separator, an increase in the internal resistance of the battery, and a low peeling strength, which easily leads to the problem of coating peeling.
By adopting the preparation method of solid electrolyte-coated separator, LLZTO is uniformly dispersed in a polyacrylonitrile solution to coat and modify it, mixed with Si3N4 and binder, and coated on the surface of the base film to form a separator with high heat resistance, peel strength and good ion transport channel.
The separator is achieved under high temperature conditions with low shrinkage and high heat resistance, which reduces the DC resistance of the battery, improves the rate performance and cycle stability, and improves the peel strength of the coating.
Smart Images

Figure CN119651047A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a solid electrolyte coated diaphragm, a preparation method thereof and a lithium ion battery. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] As one of the four main materials of lithium-ion batteries, the separator not only has the function of providing lithium-ion channels, but also has the function of isolating the positive and negative electrodes and preventing the positive and negative electrodes from short-circuiting due to contact. With the upgrade of the energy density and rate performance of the battery system, the heat generated by the battery cell under working conditions increases, so the safety of each battery component must also be further improved.
[0004] At present, large-scale commercial diaphragm materials are mainly polyethylene and polypropylene. However, due to the melting point limitation of such materials, when the temperature inside the battery rises to a certain level, the thermal shrinkage of the diaphragm is large. At the same time, lithium deposition occurs at the negative electrode under high-rate conditions for a long time, which will cause a short circuit between the positive and negative electrodes. In order to improve the dimensional stability of the diaphragm, a common method is to coat such diaphragms with ceramics and organics to improve the thermal stability of the diaphragm itself. However, with the upgrading of battery material systems, the demand for battery safety performance has been further improved. However, the current ceramic / organic coated diaphragms have poor heat resistance in a higher temperature range (T>150°C), and the ceramic / organic coated diaphragms will cause the lithium ion pass rate of the diaphragm to decrease, thereby increasing the internal resistance of the battery and adversely affecting the battery performance. In addition, the interface bonding between ceramic particles and organic matter is poor, and the peeling strength is low, which easily causes the problem of coating shedding. Therefore, it is urgent to provide a diaphragm with high heat resistance, high peeling strength and the ability to improve the problem of lithium dendrite deposition during long battery cycles. Summary of the invention
[0005] In view of this, the present invention provides a solid electrolyte coated diaphragm, a preparation method thereof and a lithium ion battery. The solid electrolyte coated diaphragm provided by the present invention has good heat resistance, high coating peel strength and needle puncture strength, has a low direct current internal resistance (DCR) when applied to lithium ion batteries, and exhibits excellent cycle stability.
[0006] In a first aspect, the present invention provides a method for preparing a solid electrolyte coated diaphragm, comprising the following steps:
[0007] S1. Dispersing LLZTO uniformly in a polyacrylonitrile solution, and drying to obtain polyacrylonitrile-coated LLZTO particles; wherein the mass ratio of LLZTO to polyacrylonitrile is (15-25):1;
[0008] S2. Mix the polyacrylonitrile-coated LLZTO particles, Si3N4 and a binder in water at a mass ratio of (5-7):(2-4):1, and then apply them to at least one side of the base film, and dry them to obtain a solid electrolyte coated diaphragm.
[0009] In a second aspect, the present invention provides a solid electrolyte coated diaphragm prepared by the above preparation method.
[0010] In a third aspect, the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode and a separator, wherein the separator is the above-mentioned solid electrolyte coated separator.
[0011] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0012] The present invention prepares PAN-coated modified LLZTO and silicon nitride particles (Si3N4) into a slurry and coats it on the surface of a base film to prepare a solid electrolyte coated diaphragm, wherein the silicon nitride particles have high thermal stability, which can effectively improve the heat resistance of the diaphragm, so that it still has a low shrinkage rate when the temperature exceeds 150°C; in addition, the silicon nitride particles can also be uniformly dispersed in the diaphragm to provide a good ion transmission channel, which can also reduce the internal resistance of the diaphragm and improve the rate performance of the diaphragm; the LLZTO coated with PAN can be uniformly dispersed on the surface of the diaphragm, effectively exert its excellent ionic conductivity, and at the same time can further improve the peel strength of the coating; the solid electrolyte coated diaphragm obtained by adjusting the appropriate ratio has high heat resistance, high puncture strength and good ionic conductivity, and the battery assembled using the same has a low direct current internal resistance (DCR) and a long cycle life; and the preparation method of the present invention is very simple and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0014] Figure 1 This is a surface scanning electron microscope image of the LLZTO-Si3N4 mixed coating diaphragm prepared in Example 1 of the present invention;
[0015] Figure 2This is a scanning electron microscope image of the cross section of the LLZTO-Si3N4 mixed coated diaphragm prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0016] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0017] The present invention provides a method for preparing a solid electrolyte coated diaphragm, comprising the following steps:
[0018] S1. Dispersing LLZTO uniformly in a polyacrylonitrile solution, and drying to obtain polyacrylonitrile-coated LLZTO particles; wherein the mass ratio of LLZTO to polyacrylonitrile is (15-25):1;
[0019] S2. Mix the polyacrylonitrile-coated LLZTO particles, Si3N4 and a binder in water at a mass ratio of (5-7):(2-4):1, and then apply them to at least one side of the base film, and dry them to obtain a solid electrolyte coated diaphragm.
[0020] LLZTO is a tantalum-doped lithium lanthanum zirconium oxide, which belongs to garnet-type oxide, has high ionic conductivity and good chemical stability. The present invention first uses polyacrylonitrile (PAN) to coat and modify LLZTO. LLZTO is insoluble in polyacrylonitrile solution, and is evenly dispersed in polyacrylonitrile solution. The macromolecular chain of polyacrylonitrile in the solution is in a stretched state, and after the solvent evaporates, it will be evenly coated on the surface of LLZTO. PAN coating not only enhances the dispersibility of LLZTO, making it evenly dispersed in the solid electrolyte coated diaphragm, but also significantly enhances the peel strength of the solid electrolyte coated diaphragm. The mass ratio of PAN to LLZTO will have a significant impact on the performance. If the PAN content is too low, it is difficult to effectively coat LLZTO, and the performance improvement is not obvious; if the PAN content is too high, it will cause the electrochemical performance of the battery to decrease, which is not conducive to application; the mass ratio of LLZTO to polyacrylonitrile is more preferably (18-22):1.
[0021] The present invention uses Si3N4 as heat-resistant particles. Si3N4 itself has excellent thermal stability, its decomposition temperature is higher than 1000°C, and it has good insulation. The present invention finds that when it is introduced into the solid electrolyte coated diaphragm of the present invention, it can not only significantly improve the heat resistance of the diaphragm, but also reduce the internal resistance of the battery. Moreover, it can be evenly dispersed in the coated diaphragm, improve the lithium dendrite deposition phenomenon, and make the battery have a longer service life. The mass ratio of polyacrylonitrile-coated LLZTO particles to Si3N4 will also affect the performance of the diaphragm and the battery. Excessive Si3N4 will cause the electrochemical performance of the battery to decrease, and too little Si3N4 will cause the heat resistance of the diaphragm to be not significantly improved, and the heat resistance is poor under conditions above 150°C.
[0022] In the present invention, the solvent of the polyacrylonitrile solution is selected from one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA) or dimethyl sulfoxide (DMSO), and the above solvents have a good dissolving effect on polyacrylonitrile. The concentration of the polyacrylonitrile solution is 0.5-5wt%, more preferably 0.8-2.5wt%. The above concentration ensures that LLZTO can be evenly dispersed and PAN is coated on the surface of LLZTO. The present invention does not impose any special restrictions on the preparation process of the polyacrylonitrile solution, and those skilled in the art can use conventional methods for preparing polyacrylonitrile solutions.
[0023] In step S2 of the present invention, polyacrylonitrile-coated LLZTO particles, Si3N4 and a binder are mixed to prepare an aqueous slurry. This is to avoid damage to the coating structure of PAN on the surface of LLZTO in an organic solvent, which affects the electrochemical properties of the diaphragm. Therefore, the binder selected in the present invention should be an aqueous binder. Preferably, the binder is selected from one or more of carboxymethyl cellulose (CMC), styrene-butadiene rubber emulsion (SBR), polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyacrylic acid (PAA) or hydroxypropyl methylcellulose (HPMC). In one or more embodiments of the present invention, the binder is selected from carboxymethyl cellulose and styrene-butadiene rubber emulsion, and the mass ratio of carboxymethyl cellulose to styrene-butadiene rubber emulsion is 1: (0.5-1.5).
[0024] In the present invention, the base film is selected from any one of polyethylene diaphragm, polypropylene diaphragm, polypropylene / polyethylene / polypropylene composite diaphragm, polyimide diaphragm, polyvinylidene fluoride diaphragm, polyethylene non-woven diaphragm, polypropylene non-woven diaphragm, and polyimide non-woven diaphragm. Those skilled in the art can select according to specific needs.
[0025] In the present invention, the particle size of LLZTO is 100-400nm, and the particle size of Si3N4 is 200-600nm. The appropriate particle size can form a good pore structure after the slurry is dried, which is beneficial to the transmission of lithium ions.
[0026] In the present invention, the coating thickness of the solid electrolyte coated diaphragm is 0.8 to 3 μm. The coating thickness should not be too thin, otherwise the protective effect on the base film is not obvious, nor too thick, otherwise it will increase the internal resistance of the battery, which is not conducive to the transmission of lithium ions and has an adverse effect on the battery performance.
[0027] In the present invention, the drying temperature in step S1 and step S2 is 50-70° C. The present invention does not impose any special restrictions on the specific drying method, and ordinary drying or vacuum drying can be adopted; the present invention does not impose any special restrictions on the specific drying time, as long as the solvent is fully volatilized.
[0028] The present invention also provides a solid electrolyte coated diaphragm prepared by the above preparation method. The solid electrolyte coated diaphragm provided by the present invention still has a low shrinkage rate when the temperature exceeds 150°C, and has high needle puncture strength and peel strength.
[0029] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and a separator, wherein the separator is the above-mentioned solid electrolyte coated separator.
[0030] The present invention has no particular limitation on the positive electrode, and any positive electrode for lithium-ion batteries known to those skilled in the art may be used, such as one or more of a lithium iron phosphate positive electrode, a nickel-cobalt-manganese ternary positive electrode, a lithium cobalt oxide positive electrode, a lithium nickel oxide positive electrode, or a lithium manganese oxide positive electrode.
[0031] The present invention has no special limitation on the negative electrode, and any negative electrode for lithium-ion batteries known to those skilled in the art can be used, such as one or more of graphite, silicon-carbon composites, and mesophase pitch carbon microspheres.
[0032] The lithium ion battery provided by the present invention has a lower DC internal resistance and good cycle stability. After 500 cycles under the charge and discharge conditions of 1C / 4C, the capacity retention rate can still be above 90%.
[0033] The technical solution of the present invention is further described below in conjunction with specific examples. The present invention has no particular limitation on the sources of the reagents used in the following examples, and commercially available products known to those skilled in the art can be used.
[0034] In the following examples, the chemical formula of LLZTO is Li 6.4 Ln3Z 1.4 Ta 0.6 O 12, its average particle size is about 250nm; the average particle size of Si3N4 is about 400nm.
[0035] Example 1
[0036] This embodiment provides a method for preparing a solid electrolyte coated diaphragm.
[0037] (1) LLZTO was added to a 1 wt% PAN solution in N-methylpyrrolidone (NMP), and the mass ratio of LLZTO to PAN was controlled to be 20:1. After continuous stirring for 4 h, a mixed dispersion was obtained, which was then placed in a vacuum oven at 60 °C. After the solvent evaporated, the PAN-coated modified LLZTO was obtained by grinding.
[0038] (2) The PAN-coated modified LLZTO obtained in step (1) was mixed with Si3N4, SBR, and CMC in a mass ratio of 7:2:0.6:0.4, and then added to deionized water, stirred at 250 r / min for 20 min to obtain an aqueous slurry, and the aqueous slurry was coated on both sides of a polyethylene base film by a gravure roller, and dried at 55°C to obtain a LLZTO-Si3N4 mixed coated diaphragm.
[0039] Figure 1 This is a surface scanning electron microscope image of the LLZTO-Si3N4 mixed coated diaphragm prepared in this example. It can be seen that a dense protective layer is formed on the surface of the base membrane layer, while maintaining a rich pore structure.
[0040] Figure 2 This is a scanning electron microscope picture of the cross section of the LLZTO-Si3N4 mixed coated diaphragm prepared in this example. It can be seen that the coating layer thickness is about 1 μm.
[0041] Example 2
[0042] This embodiment provides a method for preparing a solid electrolyte coated diaphragm.
[0043] (1) LLZTO was added to a 1 wt% PAN solution in N-methylpyrrolidone (NMP), and the mass ratio of LLZTO to PAN was controlled to be 20:1. After continuous stirring for 4 h, a mixed dispersion was obtained, which was then placed in a vacuum oven at 60 °C. After the solvent evaporated, the PAN-coated modified LLZTO was obtained by grinding.
[0044] (2) The PAN-coated modified LLZTO obtained in step (1) was mixed with Si3N4, SBR, and CMC in a mass ratio of 6:3:0.6:0.4, and then added to deionized water, stirred at 250 r / min for 20 min to obtain an aqueous slurry, and the aqueous slurry was coated on both sides of a polyethylene base film by a gravure roller, and dried at 55°C to obtain a LLZTO-Si3N4 mixed coated diaphragm, and the coating layer thickness was 1 μm.
[0045] Example 3
[0046] This embodiment provides a method for preparing a solid electrolyte coated diaphragm.
[0047] (1) LLZTO was added to a 1 wt% PAN solution in N-methylpyrrolidone (NMP), and the mass ratio of LLZTO to PAN was controlled to be 20:1. After continuous stirring for 4 h, a mixed dispersion was obtained, which was then placed in a vacuum oven at 60 °C. After the solvent evaporated, the PAN-coated modified LLZTO was obtained by grinding.
[0048] (2) The PAN-coated modified LLZTO obtained in step (1) was mixed with Si3N4, SBR, and CMC in a mass ratio of 5:4:0.6:0.4, and then added to deionized water, stirred at 250 r / min for 20 min to obtain an aqueous slurry, and the aqueous slurry was coated on both sides of a polyethylene base film by a gravure roller, and dried at 55°C to obtain a LLZTO-Si3N4 mixed coated diaphragm, and the coating layer thickness was 1 μm.
[0049] Comparative Example 1
[0050] The difference between this comparative example and Example 1 is that in step (1) of this comparative example, the mass ratio of LLZTO to PAN is 10:1.
[0051] Comparative Example 2
[0052] The difference between this comparative example and Example 1 is that in this comparative example, the PAN-coated modified LLZTO obtained in step (1) is mixed with Si3N4, SBR and CMC in a mass ratio of 8:1:0.6:0.4 and then added into deionized water.
[0053] Comparative Example 3
[0054] In this comparative example, the aluminum oxide coated diaphragm is prepared by using the existing diaphragm preparation process.
[0055] (1) 37 wt% polyethylene resin, 3% boehmite, and 60 wt% paraffin oil were mixed and put into an extruder for melt blending and extruded through a die. The mixing temperature T = 200°C and the stirring speed was 100 rpm. The viscosity average molecular weight of the polyethylene resin was 2 million.
[0056] (2) The sheet in step 1 is biaxially stretched at a stretching temperature of 200° C. and a stretching ratio of 8 times.
[0057] (3) The material in step 2 is immersed in dichloromethane for extraction, and then dried. The extraction temperature is room temperature, and the drying temperature is 40°C.
[0058] (4) The material in step 3 is biaxially stretched and shaped, the stretching temperature is 200°C, the stretching ratio is 8 times, and the shaping temperature is 130°C.
[0059] (5) Preparation of coating slurry: Add 35wt% Al2O3, 1wt% sodium dodecyl sulfate dispersant, and 5% sodium carboxymethyl cellulose to deionized water, stir and mix, and prepare alumina slurry for standby use. Mixing temperature T = 55°C, stirring speed n = 300 rpm, stirring time t = 50 min.
[0060] (6) The slurry coated in step (5) is evenly dispersed on both sides of the diaphragm by roller coating or spray coating with the aid of a gravure roller or a rotary nozzle device, and finally dried in an oven. The pre-drying temperature is T = 95°C, and the coating thickness is 3 μm.
[0061] (7) Rolling up the material in step (6).
[0062] Comparative Example 4
[0063] In this comparative example, the base film is prepared by using the existing diaphragm preparation process.
[0064] (1) 40 wt% polyethylene resin and 60 wt% paraffin oil were mixed and put into an extruder for melt blending, and the melt after mixing was melt A. The mixing temperature T = 340°C, the stirring speed n = 100 rpm. The viscosity average molecular weight of the polyethylene resin was 1,650,000.
[0065] (2) 30 wt% polyethylene resin and 70 wt% paraffin oil were mixed and put into an extruder for melt blending, and the melt after mixing was melt B. The mixing temperature T = 190°C, the stirring speed n = 75 rpm. The viscosity average molecular weight of the polyethylene resin was 1,200,000.
[0066] (3) Melt A and melt B are extruded through a three-cavity co-extrusion die to form an A / B / A structure sheet at a compounding temperature of 190°C.
[0067] (4) The sheet in step (3) is biaxially stretched at a stretching temperature of 200° C. and a stretching ratio of 8 times.
[0068] (5) The material in step (4) is immersed in dichloromethane for extraction, and then dried. The extraction temperature is room temperature, and the drying temperature is 40°C.
[0069] (6) The material in step (5) was modified by immersing it in a silane coupling agent KH550 containing 2 wt % vinyl acetate for 5 min. After immersion, the material was dried.
[0070] (7) Drying the material in step (6).
[0071] (8) The material in step (7) is biaxially stretched and shaped, with a stretching temperature of 180°C, a stretching ratio of 10 times, and a shaping temperature of 120°C.
[0072] (9) Roll up the material in step (8).
[0073] Test example
[0074] 1. Test of diaphragm performance:
[0075] (1) Acupuncture intensity:
[0076] The solid electrolyte coated diaphragms of the embodiments and comparative examples were used as experimental samples, and the puncture strength of the samples was tested with a universal tester and recorded.
[0077] (2) Peel strength:
[0078] The solid electrolyte coated diaphragms of the embodiments and comparative examples were used as experimental samples, the coating surface of the samples was pasted on the template, the solid electrolyte coated diaphragms were pulled apart at 180° using a tensile testing machine, and the tensile force when the solid electrolyte coated diaphragm was separated from the coating was recorded.
[0079] (3) Thermal shrinkage:
[0080] The solid electrolyte coated diaphragms of the embodiment and the comparative example were used as experimental samples, and the initial sizes of the samples were recorded respectively. The samples were placed in an oven and baked at 160° C. for 1 h, and the sizes after baking were compared with the initial sizes, and the thermal shrinkage rates were recorded.
[0081] (4) Membrane breaking temperature:
[0082] The diaphragms of the embodiment and the comparative example were placed as experimental specimens in the fixture of a closed-cell membrane rupture testing machine, and standard electrolyte was added. The temperature began to rise, with a temperature of 0-200°C, a rise time of 5°C / min, and a resistance range of 0-200000Ω. The diaphragm temperature-resistance curve was recorded, and the temperature corresponding to the resistance mutation point was taken as the diaphragm rupture temperature.
[0083] The test results are shown in Table 1.
[0084] Table 1 Test results of solid electrolyte coated diaphragm performance of examples and comparative examples
[0085]
[0086]
[0087] 2. Battery performance measurement:
[0088] Preparation of lithium-ion batteries: lithium iron phosphate (LFP), carbon nanotubes, conductive carbon black, and polyvinylidene fluoride are homogenized in a mass ratio of 96.2:0.5:1.5:1.8, and then coated, slitting, and die-cutting to form positive electrode sheets; graphite, conductive carbon black, styrene-butadiene latex, and sodium carboxymethyl cellulose are homogenized in a mass ratio of 96.2:0.8:1.8:1.2, and then coated, slitting, and die-cutting to form negative electrode sheets; the positive electrode sheets, negative electrode sheets, and the solid electrolyte-coated diaphragms of the embodiments or comparative examples are stacked to form a battery cell, and the required lithium-ion batteries are prepared for testing after welding, packaging, liquid injection, formation, secondary sealing, and capacity division.
[0089] (1) DC internal resistance (DCR) measurement:
[0090] The test voltage range is 2.0~3.2V, the charge rate is 1C, the discharge rate is 4C under the condition of discharge depth DOD=50%, the test temperature is -20℃, and the results are output after testing with a lithium battery detector.
[0091] (2) Cycle performance measurement:
[0092] The test voltage range is 2.0~3.2V, the charge rate is 1C, the discharge rate is 4C, the temperature is 25℃, and the results are output after testing with a lithium battery detector.
[0093] The test results are shown in Table 2.
[0094] Table 2 Performance test results of lithium-ion batteries assembled with solid electrolyte coated diaphragms in the examples and comparative examples
[0095]
[0096] It can be found from Table 2 that when the content of PAN is too high, the cycle performance will be reduced. The introduction of Si3N4 will have a certain impact on the cycle performance, but the capacity retention rate can still be above 90% after 500 cycles under 1C / 4C charge and discharge conditions. This is because the addition of LLZTO improves the permeability of lithium ions and slows down the rate of lithium deposition on the negative electrode side. In addition, the compactness of the mixed coating material also makes the diaphragm have better needle puncture strength in the lithium battery, thereby further improving the overall safety of the lithium battery. It can also be seen from Table 2 that the coated diaphragm prepared in the embodiment has significantly better cycle performance than the alumina coated diaphragm and polyethylene-based film prepared by the traditional process.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a solid electrolyte coated diaphragm, characterized in that: The steps include: S1. Dispersing LLZTO uniformly in a polyacrylonitrile solution, and drying to obtain polyacrylonitrile-coated LLZTO particles; wherein the mass ratio of LLZTO to polyacrylonitrile is (15-25):1; S2. Mix the polyacrylonitrile-coated LLZTO particles, Si3N4 and a binder in water at a mass ratio of (5-7):(2-4):1, and then apply them to at least one side of the base film, and dry them to obtain a solid electrolyte coated diaphragm.
2. The preparation method according to claim 1, characterized in that The solvent of the polyacrylonitrile solution is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide; the concentration of the polyacrylonitrile solution is 0.5-5wt%.
3. The preparation method according to claim 1, characterized in that: The binder is selected from one or more of carboxymethyl cellulose, styrene-butadiene rubber latex, polyvinyl alcohol, polyvinyl pyrrolidone, polyacrylic acid or hydroxypropyl methyl cellulose.
4. The preparation method according to claim 3, characterized in that: The binder is selected from carboxymethyl cellulose and styrene-butadiene rubber emulsion, and the mass ratio of the carboxymethyl cellulose to the styrene-butadiene rubber emulsion is 1:(0.5-1.5).
5. The preparation method according to claim 1, characterized in that: The base film is selected from any one of polyethylene membrane, polypropylene membrane, polypropylene / polyethylene / polypropylene composite membrane, polyimide membrane, polyvinylidene fluoride membrane, polyethylene non-woven membrane, polypropylene non-woven membrane and polyimide non-woven membrane.
6. The preparation method according to claim 1, characterized in that: The particle size of the LLZTO is 100-400 nm, and the particle size of the Si3N4 is 200-600 nm.
7. The preparation method according to claim 1, characterized in that: The coating layer thickness of the solid electrolyte coated diaphragm is 0.8-3 μm.
8. The preparation method according to claim 1, characterized in that: The drying temperature in step S1 and step S2 is 50-70°C.
9. The solid electrolyte coated diaphragm prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium ion battery comprising a positive electrode, a negative electrode and a separator, characterized in that: The diaphragm is the solid electrolyte coated diaphragm according to claim 9.
Citation Information
Patent Citations
Composite coating diaphragm with consistent pore diameter and preparation method thereof
CN111244365A
Composite solid-state electrolyte membrane, preparation method thereof and solid-state battery
CN113314764A
Modified diaphragm for lithium battery and preparation method of modified diaphragm
CN116864922A
Solid electrolyte membrane, preparation method thereof and secondary battery
CN118486884A
Battery diaphragm with porous ceramic modified coating and preparation method of battery diaphragm
CN118983621A
Cited By
An asymmetric dual-function coated separator, its preparation method and application
CN122512119A